Health panorama of riverside populations in the Brazilian Amazon and applicable social technologies (Research, Society and Development, 2020)
As great as the enchantments and dimensions of the Amazon are the limitations on access to basic sanitation systems that its riverside population faces, so the following question arises: are there solutions capable of meeting the needs of this population more immediately? Within this perspective are Social Technologies, which are methodologies, products or techniques developed in conjunction with the communities served and present themselves as simple and low-cost alternatives for solving problems. The objective of this research is to present the characteristics and a brief health panorama of the riverside population of the Brazilian Amazon, as well as to carry out a survey of the social technologies developed to meet their needs in the scope of basic sanitation. A descriptive and bibliographic research was carried out, focusing on information related to riverside communities only in the Brazilian Amazon. Poor levels of sanitary sewage, and the inability or lack of public policies are evidenced in the studies on these communities, leaving the population only to resort to the habits that are available to them and that favor the appearance of diseases. When analyzing the social technologies found, there is a notable discrepancy between the amount of experience according to the purpose for which it is intended within the aspects of sanitation. In short, difficulty of access, inadequate conditions and / or lack of basic sanitation systems, lack of electricity and health services, are predominant factors in the housing areas of riverside populations. Thus, the implementation of social technologies are valuable tools for meeting these needs.